Development of Animaker-Based Animated Video and Team Quiz Activities to Improve Mastery of Static Fluid Concepts - Amedia, Frisca; Zakaria, Rosnah; Subali, Bambang; Linuwih, Suharto; Ellianawati, Ellianawati (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2023)
This study aims to discover the characteristics of Animaker-based animated video, explore opportunities, measure feasibility and effectiveness, and analyze students’ responses to Animaker-based animated video and quiz team activities in improving the static fluid concept’s mastery. The method used in this research is R&D with the ADDIE development model. The result of this research shows that Animaker-based animated video and quiz team activities have the opportunity to improve the mastery of static fluid concepts. The characteristics of Animaker-based animated video media are shown in each part of the video, such as a teacher’s animation, process illustration, case study, practice questions, and simulation examples. The average validation score from three media experts is 87.1%, meaning the Animaker-based animated video is highly feasible. Animaker-based animated video media and team activities quizzes effectively improve the mastery of static fluid concepts. Student responses get a percentage of 82% in the very good category.